ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGELOLAAN PAMSIMAS DI DESA BANGLAS BARAT KECAMATAN TEBING TINGGI KABUPATEN KEPULAUAN MERANTI - ', Sukarman; Wicaksono, Baskoro (Universitas Riau, 2017)
This research is motivated target PAMSIMAS village election in the village of Banglas Baratyears 2014-2016 in accordance with the decree of the minister of public works decree No. 79 /Kpts / DC / 2013 on stipulation district / city target PAMSIMAS. Implementers programPAMSIMAS at the district level conducted by the planning office and the department of publichealth office of human settlements POKJA AMPL is incorporated in regency Kepulauan Meranti,while implementers at the village level is done by the village government, KKM, SATLAK,BPSPAMS and community facilitator team. The research directs the factors that influence themanagement of the PAMSIMAS program. Research to know the factors that influence themanagement of PAMSIMAS program.The type used in this research is descriptive research withqualitative research approach. Type of research data is primary data and secondary data. Datacollection techniques in this study is documentation and interviews. Technical analysis of the dataused is descriptive qualitative data analysis. The result of the research shows that there areseveral factors that influence the management of PAMSIMAS in terms of the content of the benefitfactor policy and the degree of change to be achieved which is still a constraint, while in terms ofpolicy environment the role of Village Government and Local Government is still minimal indoing support in terms of material as well development of PAMSIMAS facilities that have notbeen able to reach all PAMSIMAS beneficiaries.